THE IMPACT OF ENVIRONMENTAL CHANGES ON BLACK MARLIN, Makaira indica (Cuvier, 1832) ABUNDANCES IN THE EASTERN INDIAN OCEAN - Bram Setyadji; Zulkarnaen Fahmi (Indonesian Fisheries Research Journal, 2020)
Black marlin (Makaira indica) is commonly caught as frozen by-catch from Indonesian tuna longline fleets. Its contribution estimated 18% (~2,500 tons) from total catch in Indian Ocean. Relative abundance indices as calculated based on commercial catches are the input data for several to run stock assessment analyses that provide models to gather information useful information for decision making and fishery management, however, little are known about the influence of environmental factors to its abundance. In this paper, the abundance was represented as standardized index in order to eliminate any bias on other factors which might influence it. Data were collected from August 2005 to December 2017 through scientific observer program (2005-2017) and national observer program (2016-2017). Most of the vessels monitored were based in Benoa Port, Bali. Overall, time trends of abundance was fluctuated, although, there was increasing trend since 2010 then dropped significantly into relatively similar figure in 2005. Even though, Sea Surface Temperature (SST) and Sea Surface Height (SSH) were statistically significant when incorporating into the models, but it allegedly wasn’t the main driver in determining the abundance of black marlin. Instead, it was more likely driven by spatio-temporal factors (year and area) effect rather than environmental changes.